Revisiting Financial Inclusion: Does Socio-economic Development Matter? - Ayushi Raichoudhury (Vikalpa)
The article attempts to measure financial inclusion at the household level with the Wroclaw taxonomic approach as an appropriate method of construction of composite indices and study the effects of various socio-economic development indicators on financial inclusion at the disaggregated level. Data analysis exemplified that the level of financial inclusion was directly related to per-capita income, household amenities, literacy and awareness of Pradhan Mantri Jan Dhan Yojana (PMJDY) and inversely to the distance from the bank (beyond 3 km). The results also suggested that the intended outcome of creating awareness about PMJDY to promote financial inclusion was not achieved in rural areas.